Heartful Visits: a volunteering program to enhance student interpersonal skills and reduce patient isolation through non-clinical encounters (Canadian Medical Education Journal, 2025)
Implication StatementTo enhance students’ interpersonal skills and reduce hospitalized patients’ feeling of isolation, we developed Heartful Visits, an on-campus healthcare volunteer coordination hub that organizes non-clinical visits focused on conversations, companionship, and emotional support. In this paper, we will detail its design, implementation, and early outcomes to provide a replicable methodology and to inspire medical students at other universities to adapt and expand upon this model. Through this dual focus on student education and patient care, the program has the potential to improve student empathy and communication skills, along with reducing patient isolation and improving psychosocial wellbeing.